Hipokritisme Tokoh Orientalis Christiaan Snouck Hurgronje - Budi Ichwayudi (Religió: Jurnal Studi Agama-agama, 2011)
Western thoughts have discredited Islamic teaching. Orientalism never gives up in spreading issues in relation with their objectives in distancing Muslim from Islam. The idea of orientalism becomes a point of discussion that appears as opposition of Islam in many ways. Unfortunately, this kind of situation has not been realized by most Muslim in Indonesia that is contemporarily bothered by their debated teaching of Islam which comes from orientalist ideas in order to disintegrate Islam. For instance, is the orientalism in Indonesia. The history of orientalism in Indonesia becomes unforgettable part of Indonesia colonialism. It was known that the orientalist activities have supplied many objectives for the colonialism, especially in Aceh Darussalam. Hurgronje analyzed and observed that the struggle from the Acehness will be suppressed by the politics of split within the local leader between Ulama (religious leader) and Uleebalang (formal leader). This paper aims to explore the activities of Christian Snouck Hurgronje in relation with his effort in helping colonial to disintegrate Indonesia people. His mission is to crack the principal sources of Islam: Qur’an and Hadith by pretending to be a Muslim and went to Mecca for learning Islam. But his affiliation to Islam is only a mask to cover his actual purposes as a missionary.